Efeitos in vitro e in vivo do bissulfato de clopidogrel em modelo experimental de melanoma: envolvimento do sistema purinérgico plaquetário - Jantsch, Matheus Henrique (2022)
Melanoma is a type of cancer that, when it develops into the metastatic form, is very aggressive and makes conventional antitumor treatments less effective. Activated platelets are involved in tumor progression through cellular interactions and secretion of nucleosides and nucleotides, such as ATP, ADP, and adenosine. The extracellular concentration of these substances is controlled by enzymes that make up the purinergic system and are present on the cell surface. Nucleotides and nucleoside interact with receptors on the surface of cells and platelets and are recognized as purinergic receptors. Clopidogrel bisulfate (CB) is na inhibitor of the P2Y12 purinergic receptor, so it can be used to inhibit platelet activation. Thus, this project aimed to investigate the effect of BC in vitro and in vivo on tumor progression and modulation of enzymes of the purinergic pathway (CD39, CD73, E-ADA) in platelets. The in vitro study was performed with B16-F10 cells treated with 7 concentrations of CB and assessed after 24h, 48h, and 72h. The in vivo study was conducted with mice (C57BL-6), which were divided into 4 groups: negative control (C); melanoma control (M); treated with CB (BC); with melanoma treated with BC (M+BC). Cancer induction in the groups with melanoma was performed by administration of B16-F10 cells by intraperitoneal route. After 2 days, treatment with BC at a dose of 30mg/kg/day was initiated by gavage for 12 days. At the end of this period, the animals were anesthetized and euthanized by exsanguination for evaluation of parameters such as tumor nodule count, organ weight, blood count, quantification of plasma biomarkers: lactate dehydrogenase (LDH); nitric oxide (ON); and reactive oxygen species (ROS), and assessment of the activity of enzymes of the purinergic system (NTPDase, 5'-nucleotidase, E-ADA) in platelets. In in vitro B16-F10 cultures, BC decreased proliferation in 72 h and increased cell cytotoxicity at doses greater than 30 μM. In vivo, the treatment decreased tumor nodule count, increased NO levels, and decreased LDH activity. However, BC treatment was not effective in reducing the systemic effects of induction, as reflected in blood count and organ weights. Higher activity of purinergic enzymes in platelets was also observed compared to the untreated groups. Thus, BC treatment appears to reduce potential alterations associated with tumor progression, suggesting a beneficial effect in the treatment of melanoma.